A functional analysis of the effects of the molecular weight of dextran on ε-polylysine-dextran conjugate created through the maillard reaction. (1st October 2022) - Yan, Chengying; Ding, Chuandi; Cheng, Chen; Gong, Yujie; Han, Shuangxia; Xia, Zhiyuan; Kang, Dacheng
Highlights: Mw of dextran is the main factor affect the formation of PL-dextran conjugate. HMD and LMD possessed a higher reaction rate of Millard reaction than MMD. Conjugate of HMD-PL exhibit better emulsifying activity than that of MMD and LMD. Conjugate of LMD-PL exhibit better antimicrobial activity than that of HMD and MMD. Abstract: The present study mainly examines the effects of molecular weight of dextran on the reaction rate and functional characteristics between ε-polylysine (PL) and dextran. The reaction kinetics, grafting degree and gel permeation chromatography are employed to evaluate the reaction rate and extent of these lard reaction. We find low activation energy ( Ea ) values that indicate that dextran with high molecular weight (HMD) exhibits a higher reaction rate with PL than that that of dextran with middle molecular weight (MMD) and low molecular weight (LMD). As for the functional characteristics of the formed conjugate, the conjugate of PL-HMD possesses a higher emulsifying activity, and PL-LMD exhibits higher antimicrobial activity than other molecular weight of dextran. We observe that long heating time at high temperatures can induce the partial degradation of the formed conjugates, which is reflected in the decreasing of the emulsifying and antimicrobial activity of PL-dextran conjugates.